Quality of life of Chronic Kidney Disease patients attending Nephrology OPD of a tertiary care centre in Western Maharashtra - Shivam Salaria; Surabhi Sharma; Gurmesh Singh Sabharwal; Suraj Kumar Dubey; Puja Dudeja; Vipra Mangla (Al Ameen Medical College, 2023)
Introduction: Kidney disease is a global public health problem affecting approximately 750 million people worldwide. Patients of Chronic Kidney Disease (CKD) face bio-psychological stressors affecting their quality of life (QoL). CKD patients with low QoL have shown considerably high mortality. Assessing QoL can help in planning holistic medical care for these patients and improve disease outcomes. The present study has been conducted with the objective to assess QoL in CKD patients. Objective: To assess QoL of CKD patients attending Nephrology OPD of a tertiary care Government centre in Western Maharashtra. Methodology: It was a cross-sectional descriptive study conducted in Nephrology OPD of a tertiary care hospital in Western Maharashtra. Pre-tested Research and Development Corporation 36-item Health Survey Questionnaire was self- administered to CKD patients and QoL scores were calculated. All patients attending Nephrology OPD were included in the study group from July to Oct 2019. Data was analysed using SPSS version 20.0. Results: The study included 70 patients with moderate to advanced CKD irrespective of status of treatment being received. Diabetes Mellitus was found to be the most common cause of CKD followed by Hypertension. The mean overall QoL score was 38.9+8.2. The mean Mental Component Summary (MCS) score (29.2+7.8, 95%C.I.: 21.4-37.0 was significantly lower than the mean Physical Component Summary (PCS) score (48.5 + 9.5, 95% C.I.: 39.0-58.0, p<0.001). Conclusion: Patients with CKD have lower MCS compared to PCS.